Poly(acrylic acid)-regulated Synthesis of Rod-Like Calcium Carbonate Nanoparticles for Inducing the Osteogenic Differentiation of MC3T3-E1 Cells - Yang, Wei (Int J Mol Sci, 2016)
Calcium carbonate, especially with nanostructure, has been considered as a good candidate material for bone regeneration due to its excellent biodegradability and osteoconductivity. In this study, rod-like calcium carbonate nanoparticles (Rod-CC NPs) with desired water dispersibility were achieved with the regulation of poly (acrylic acid). Characterization results revealed that the Rod-CC NPs had an average length of 240 nm, a width of 90 nm with an average aspect ratio of 2.60 and a negative ζ-potential of −22.25 ± 0.35 mV. The degradation study illustrated the nanoparticles degraded 23% at pH 7.4 and 45% at pH 5.6 in phosphate-buffered saline (PBS) solution within three months. When cultured with MC3T3-E1 cells, the Rod-CC NPs exhibited a positive effect on the proliferation of osteoblast cells. Alkaline phosphatase (ALP) activity assays together with the osteocalcin (OCN) and bone sialoprotein (BSP) expression observations demonstrated the nanoparticles could induce the differentiation of MC3T3-E1 cells. Our study developed well-dispersed rod-like calcium carbonate nanoparticles which have great potential to be used in bone regeneration.